2016
DOI: 10.1371/journal.pone.0147770
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence of the Ego-Depletion Effect across Task Characteristics and Individual Differences: A Pre-Registered Study

Abstract: Ego-depletion, a psychological phenomenon in which participants are less able to engage in self-control after prior exertion of self-control, has become widely popular in the scientific community as well as in the media. However, considerable debate exists among researchers as to the nature of the ego-depletion effect, and growing evidence suggests the effect may not be as strong or robust as the extant literature suggests. We examined the robustness of the ego-depletion effect and aimed to maximize the likeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(114 citation statements)
references
References 55 publications
4
104
0
1
Order By: Relevance
“…Some researchers have questioned the authenticity of the depletion effect (Carter et al, 2015). One pre-registered replication study found no evidence of an ego depletion effect (Lurquin et al, 2016). Similarly, a multi-lab pre-registered replication study found minimal evidence of a depletion effect (Hagger et al, 2016; for a commentary, see Baumeister and Vohs, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have questioned the authenticity of the depletion effect (Carter et al, 2015). One pre-registered replication study found no evidence of an ego depletion effect (Lurquin et al, 2016). Similarly, a multi-lab pre-registered replication study found minimal evidence of a depletion effect (Hagger et al, 2016; for a commentary, see Baumeister and Vohs, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Yet very little understanding of potential moderators exists (Lurquin et al, 2016). According to capacity-based theories, self-control is a dispositional, trait-like construct that differs across individuals (e.g., Tangney et al, 2004; de Ridder et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Entre aquests efectes estan, per exemple, el de la posa de poder i altres efectes similars de corporització (Rane hill, Dreber, Johannesson, Leiberg, Sul i Weber, 2015), els de depleció de l'ego (Lurquin i al., 2016), molts dels efectes de facilitació social (Rohrer, Pashler i Harris, 2015;Shanks i al., 2015) i una bona part de les intervencions psicotera pèutiques en diferents contextos d'aplicació (Van der Gucht i al., 2016;Coyne, Thombs i Hagedoorn, 2010).…”
Section: La Crisi De La Psicologia Científica I Les Seues Causes Immeunclassified
“…Cognitive effort is a far more challenging construct to define and study empirically (Botvinick & Braver, ; Dunn & Risko, ; Kurzban, ; Westbrook & Braver, ). Although many accounts have attempted to generalize the energetic aspect of physical effort accounts to cognitive effort accounts (Baumeister, Bratslavsky, Muraven, & Tice, ; Boksem & Tops, ; Gailliot & Baumeister, ), this premise has been met with a large amount of skepticism on the basis of theoretical and empirical grounds (e.g., Botvinick & Braver, ; Carter & McCullough, ; Gibson, ; Hockey, ; Inzlicht & Schmeichel, , ; Job, Walton, Bernecker, & Dweck, ; Kelly, Sünram‐Lea, & Crawford, ; Lange & Eggert, ; Lurquin et al, ; Kurzban, ; Kurzban, Duckworth, Kable, & Myers, ; Raichle & Mintun, ; Vadillo, Gold, & Osman, ; Westbrook & Braver, ). Furthermore, whether or not similar systems underlie evaluation of both physical and cognitive effort remains to be determined (Westbrook & Braver, ; cf.…”
Section: General Evaluability Theorymentioning
confidence: 99%